2017
DOI: 10.1128/genomea.00126-17
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequences of Two Closely Related Bacteria, Actinomyces sp. Strain Chiba101 and Actinomyces denticolens DSM 20671 T

Abstract: Actinomyces sp. strain Chiba101, isolated from an arthritic leg joint of a pig raised in Japan, is a bacterium closely related to Actinomyces denticolens. Here, we deciphered the complete genome sequence of Actinomyces sp. Chiba101 and the high-quality draft genome sequence of A. denticolens DSM 20671T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Reference assembly was performed using the genome of A. denticolens strain Chiba 101 (GenBank: NZ_AP017896), isolated from an arthritic leg joint of a pig raised in Japan ( 22 ) as a reference sequence. The parameters for mapping the reads were as follows: match score = 1; mismatch cost = 2; insertion open cost = 6; insertion extend cost = 1; deletion open cost = 6; deletion extend cost = 1; length fraction = 0.5; and similarity fraction = 0.8.…”
Section: Methodsmentioning
confidence: 99%
“…Reference assembly was performed using the genome of A. denticolens strain Chiba 101 (GenBank: NZ_AP017896), isolated from an arthritic leg joint of a pig raised in Japan ( 22 ) as a reference sequence. The parameters for mapping the reads were as follows: match score = 1; mismatch cost = 2; insertion open cost = 6; insertion extend cost = 1; deletion open cost = 6; deletion extend cost = 1; length fraction = 0.5; and similarity fraction = 0.8.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the homology of the data deciphered by whole-genome sequences by Kanesaki et al . [ 13 ], ANI between Actinomyces denticolens DSM 20671 T (accession number BDIO01000001 to BDIO01000008) and the strain Chiba 101 (accession number AP017896) was calculated using the ANI Calculator ( http://www.ezbiocloud.net/tools/ani ). The selected house-keeping genes, atpA (ATP synthase F1, alpha subunit, ANA_0169), metG (methionyl-tRNA synthetase, ANA 1898), rpoB (DNA-directed RNA polymerase, beta subunit, ANA_1497), pgi (glucose-6-phosphate isomerase, ANA_0727), gltA (citrate synthase I, ANA_1674), gyrA (DNA gyrase, A subunit, ANA_2224), pheS (phenylalanyl-tRNA synthetase, alpha subunit, ANA_1034) and 2 genes for fimbrial proteins, Type-2 fimbriae fimA (ANA_0024 fimbrial structural subunit) and type-1 fimbriae fimP (ANA_2510 Type-1 fimbrial major subunit precursor) of strain Chiba 101 were compared to those of the Actinomyces denticolens DSM 20671 T .…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, we found that complete genome sequences of the strain Chiba 101 and the type-strain of Actinomyces denticolens (=DSM 20671 T ) had closely related each other [ 13 ]. We speculated that Actinomyces denticolens, strain Chiba 101 and “ Actinomyces suis ” Franke 1973 could possibly belong to the same species.…”
mentioning
confidence: 99%